For a philosophy of good construction: a learning experience - Marrone, P.; Mancini, Francesco (2022)
The knowledge of construction techniques handed down its wealth of experience through manuals and codes of practice for a long time. The manuals of the past not only supported the construction through technical information but also expressed a 'philosophy' of good construction by transferring construction principles and rules into the project. The themes of good construction were enriched in the twentieth century by numerous objectives, among which the most significant are the industrialization and systematisation of building processes and the challenges of sustainability, from energy efficiency to the recycling of materials to building regeneration. In university education, however, the transmission of knowledge on construction stayed limited to lessons on the elements and construction techniques that declined in the various materials.While the recent global spread of computerization ensured the wide availability of technical information sources online, this phenomenon did not produce, per se, innovative, integrated and sustainable building solutions. The authors hypothesise that today's technical information is not ethically committed to clarifying the complex aspects of construction in sustainable terms.The proposed thesis considers architecture, like medicine, a “practice based on science and operating in a world of values” (Cosmacini, 2008).